Diet-induced inflammation: From gut to metabolic organs and the consequences for the health and longevity of ruminants. (October 2018) - Khiaosa-ard, Ratchaneewan; Zebeli, Qendrim
Abstract: Dietary shifts play an important role in decreased longevity in ruminant livestock. Ruminants evolved as cellulose fermenters adapt to fiber-rich diets. Instead, high-producing ruminants nowadays are commonly fed with grain-based diets to increase intake and productivity. Such diets, however, trade off the health of the animal. One negative aspect of such feeding is related to elevated levels of bacterial endotoxin (lipopolysaccharide, LPS) in the gut lumen and the likelihood of LPS translocation across the gut causing systemic and local (tissue) inflammation with consequences for production and longevity. However, the view for toxicity of gut LPS is oversimplified, overlooking the physicochemistry of LPS and the translocation route that determine the fate and immune reactive activity of LPS within the host. The barrier and defensive mechanisms of rumen morphology and intestinal mucus are understated. LPS cross the epithelial barrier paracellularly through impaired tight-junction and transcellularly through receptor-mediated transcytosis and the lipoprotein pathway transporting lipids. The lipoprotein pathway delivers LPS to the circulation before reaching the liver for detoxification and is believed to be the major natural route of gut LPS translocation at least in non-ruminants. Ruminant research has focused on endotoxemia and systemic inflammation but with little success and conflicting results, not to mention that low-grade inflammation is not easy to detect. In fact, LPS in the circulation must be effectively removed to avoid an adverse effect of rising level of LPS in the circulation. Circulating LPS could be transported towards target tissues in various organs, leading to local inflammation and altered metabolic activity in the tissues. Therefore, it might be feasible to capture tissue inflammation, especially in the metabolic organs including the liver, adipose tissues, and mammary gland. The present review gathers research updates and presents a comprehensive view of the physicochemical properties and bioactivity of LPS and the possibilities of translocation as well as other possible fate of LPS at each gut site in ruminants. Furthermore, we describe the involvement of three key metabolic organs including the liver, adipose tissue, and mammary gland in response to gut-derived LPS that lead to inflammation in the tissue posing consequences for the health and longevity of dairy cows. Highlights: Gut-derived endotoxins (LPS) can lead to inflammation and altered metabolic activities in tissues. The bioactivity of LPS to trigger host's cells depends on the properties and transolcation route of LPS. Article describes the physicochemical properties of LPS. Article underlines translocation routes and other fate of LPS at each gut site in ruminants. Article describes the mechanisms of LPS causing inflammation in the liver, adipose tissue and mammary gland.